Philosophical And Methodological Foundations Of Rural Health - Yusupov Murodali Sunnatovich (Peerian Journals Publishing, 2025)
The health of the rural population should be viewed not only as a medical or ecological issue, but also as a complex phenomenon requiring a philosophical and methodological approach. Human health is formed as a result of the dialectical relationship between one's biological nature, social lifestyle, and ecological environment. From this perspective, the following methodological foundations play a crucial role in analyzing the health of the rural population. The article examines the factors that have a constructive impact on the health of the rural population, analyzing the issues of the intrinsic dialectics between humans and nature, society and the individual, and biological and social phenomena.
Keywords: human; rural; rural health